2012
DOI: 10.1093/brain/awr324
|View full text |Cite
|
Sign up to set email alerts
|

The time course of retrograde trans-synaptic degeneration following occipital lobe damage in humans

Abstract: Following damage to the human post-geniculate visual pathway retrograde trans-synaptic degeneration of the optic nerve fibres occurs. It has been known for some time from investigations carried out in primates that a decline in the number of retinal ganglion cells follows occipital lobectomy. However, this is not detectable in all species studied and whether this occurs in humans was controversial until recent studies that have shown that following lesions of the occipital lobe, the retinal nerve fibre layer t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
195
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(210 citation statements)
references
References 20 publications
7
195
0
8
Order By: Relevance
“…Evidence from OCT studies also supports a role for TRD in disorders of the posterior visual pathway [34,35,67,68] with visual field defects in these disorders correlating best with macular GCL thickness than with RNFL thickness [67,68]. Likewise, OCT findings in AD suggest the contribution of TRD in the pathophysiology of visual changes.…”
Section: Pathological Changes In the Retina And Optic Nervementioning
confidence: 87%
See 1 more Smart Citation
“…Evidence from OCT studies also supports a role for TRD in disorders of the posterior visual pathway [34,35,67,68] with visual field defects in these disorders correlating best with macular GCL thickness than with RNFL thickness [67,68]. Likewise, OCT findings in AD suggest the contribution of TRD in the pathophysiology of visual changes.…”
Section: Pathological Changes In the Retina And Optic Nervementioning
confidence: 87%
“…Fletcher et al (1988) described optic disc pallor and band atrophy in individuals with congenital occipital lesions. Initially it was believed that TRD in the visual pathway occurred only in individuals with congenital (prenatal) occipital lobe lesions [33], although recent studies have also provided evidence that TRD of RGC can also occur in patients with acquired occipital lobe lesions [34][35][36].…”
Section: Pathological Changes In the Retina And Optic Nervementioning
confidence: 99%
“…ENERALLY, damage to the human central nervous system leads to retrograde trans-synaptic degeneration [1]- [4]. Optical coherence tomography (OCT) studies have revealed peripapillary retinal nerve fiber layer (pRNFL) loss in patients with various types of cerebral damage, including damage to the frontal, parietal, temporal, and occipital lobes [1], [2], [5], [6].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported that retinal thinning possibly due to RTSD is present in humans, as determined using OCT in patients with HVFDs due to lesions not involving the optic tract and LGN. 8–10,24,25 In our previous study, we reported that the inner retina corresponding to the blind visual fields demonstrated thinning within a few years after the onset of occipital damage using spectral-domain OCT. 9 Some of the patients who developed a post-geniculate lesion within 1 year of evaluation did not show inner macular thinning by OCT. 26 Meier et al found that the retinal nerve fibre layer of a patient with HVFD due to an occipital lobe abscess was thinned but no RAPD was noted after 2 years. 10 Conversely, small RAPD due to HVFDs has been detected immediately after stroke, when no retinal atrophy should be present.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, retrograde trans-synaptic degeneration (RTSD) in the patients with HVFDs has reported that the thickness of the inner layer of the retina is thinned, 8,9 but the relationship with pupillary light reflex is not clarified. If retinal ganglion cells are damaged due to RTSD, there could be corresponding pupillary defects.…”
Section: Introductionmentioning
confidence: 99%